Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the equation of a line that has a gradient (slope) of -3 and passes through the point [tex]\((-1, 4)\)[/tex], we can use the point-slope form of the linear equation. The point-slope form is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\((x_1, y_1)\)[/tex] is the point through which the line passes.
Here, we are given:
- The slope [tex]\( m = -3 \)[/tex]
- The point [tex]\((x_1, y_1) = (-1, 4)\)[/tex]
Let's substitute these values into the point-slope form equation:
[tex]\[ y - 4 = -3(x - (-1)) \][/tex]
Simplify the equation inside the parentheses:
[tex]\[ y - 4 = -3(x + 1) \][/tex]
Next, we'll distribute the slope [tex]\(-3\)[/tex] on the right side:
[tex]\[ y - 4 = -3x - 3 \][/tex]
To get the equation into the slope-intercept form [tex]\( y = mx + c \)[/tex], we'll solve for [tex]\( y \)[/tex]. To do this, we'll add 4 to both sides of the equation:
[tex]\[ y = -3x - 3 + 4 \][/tex]
Combine the constant terms on the right side:
[tex]\[ y = -3x + 1 \][/tex]
Thus, the equation of the line with a gradient of -3 passing through the point [tex]\((-1, 4)\)[/tex] is:
[tex]\[ y = -3x + 1 \][/tex]
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope, and [tex]\((x_1, y_1)\)[/tex] is the point through which the line passes.
Here, we are given:
- The slope [tex]\( m = -3 \)[/tex]
- The point [tex]\((x_1, y_1) = (-1, 4)\)[/tex]
Let's substitute these values into the point-slope form equation:
[tex]\[ y - 4 = -3(x - (-1)) \][/tex]
Simplify the equation inside the parentheses:
[tex]\[ y - 4 = -3(x + 1) \][/tex]
Next, we'll distribute the slope [tex]\(-3\)[/tex] on the right side:
[tex]\[ y - 4 = -3x - 3 \][/tex]
To get the equation into the slope-intercept form [tex]\( y = mx + c \)[/tex], we'll solve for [tex]\( y \)[/tex]. To do this, we'll add 4 to both sides of the equation:
[tex]\[ y = -3x - 3 + 4 \][/tex]
Combine the constant terms on the right side:
[tex]\[ y = -3x + 1 \][/tex]
Thus, the equation of the line with a gradient of -3 passing through the point [tex]\((-1, 4)\)[/tex] is:
[tex]\[ y = -3x + 1 \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.